SELECTIVE AMMONIA SENSOR BASED ON POROUS SILICON - TUNGSTEN OXIDE HETEROSTRUCTURE - Ibraimov М.; Khaniyev Б.; Duisebayev Т; Tileu А.; Almen Д (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
In this work, a gas sensor was fabricated based on a heterostructural material consisting of porous silicon and tungsten oxide. Porous silicon was obtained by electrochemical etching, and porous silicon/WO3 material was obtained by magnetron sputtering. The electrical and morphological characteristics of the obtained material and its sensitivity to various gases have been studied. Experimental work has shown that among several types of gas obtained as a sample, the specified gas sensor has a high sensitivity to ammonia molecules, respectively, the material under study can be used as a selective ammonia sensor.